Velocity loss as an indicator of neuromuscular fatigue during resistance training - Sanchez-Medina, L.; Gonzalez-Badillo, J. J. (Medicine & Science in Sports & Exercise, 2011)
Purpose: This study aimed to analyze the acute mechanical and metabolic response to resistance exercise protocols (REP) differing in the number of repetitions (R) performed in each set (S) with respect to the maximum predicted number (P).